Characterization of the Deep Water Surface Wave Variability in the California Current Region. Issue 11 (16th November 2017) - Villas Bôas, Ana B.; Gille, Sarah T.; Mazloff, Matthew R.; Cornuelle, Bruce D.
Abstract: Surface waves are crucial for the dynamics of the upper ocean not only because they mediate exchanges of momentum, heat, energy, and gases between the ocean and the atmosphere, but also because they determine the sea state. The surface wave field in a given region is set by the combination of local and remote forcing. The present work characterizes the seasonal variability of the deep water surface wave field in the California Current region, as retrieved from over two decades of satellite altimetry data combined with wave buoys and wave model hindcast (WaveWatch III). In particular, the extent to which the local wind modulates the variability of the significant wave height, peak period, and peak direction is assessed. During spring/summer, regional‐scale wind events of up to 10 m/s are the dominant forcing for waves off the California coast, leading to relatively short‐period waves (8–10 s) that come predominantly from the north‐northwest. The wave climatology throughout the California Current region shows average significant wave heights exceeding 2 m during most of the year, which may have implications for the planning and retrieval methods of the Surface Water and Ocean Topography (SWOT) satellite mission. Key Points: During spring/summer the sea state off the California coast is dominated by short‐period, locally generated waves up to 50% of the time These locally generated waves are forced by regional‐scale strong wind events that occur between April and July along the California Coast The significant wave height at the potential SWOT calval site is above the threshold specified for the SWOT error budget over 60% of the time